God and human dignity - Soulen, R. Kendall; Woodhead, Linda (Eerdmans, 2006)
Introduction: Contextualizing human dignity / R. Kendall Soulen, Linda Woodhead -- The Source and Scope of Human Dignity: -- The self in the Psalms and the image of God / James Luther Mays -- Recovering human dignity / Christoph Schwöbel -- Anima ecclesiastica / Robert W. Jenson -- Covenantal anthropology: integrating three contemporary discourses of human dignity / H. Russel Botman -- Creation: -- Anthropology in an evolutionary context / John Polkinghorne -- Cruising toward Bethlehem: human dignity and the new eugenics / R. Kendall Soulen -- Human dignity in the absence of agency /Hans S. Reinders -- Redemption: -- The logic of indignity and the logic of redemption / Peter Ochs -- Land, displacement, and hope in Jeremiah and in today's world / Esther Marie Menn -- God's promise for humanity in the New Testament / C. Clifton Black -- The economy of grace: human dignity in the market system / M. Douglas Meeks -- Repetition, or the theological failures of modern dignity discourse: the case of Frederick Douglass's 1845 "Narrative" / J. Kameron Carter -- Sanctification: -- Apophatic anthropology / Linda Woodhead -- Human dignity: concepts and experiences / Fraser Watts -- The "end" of the human or the end of the "human"?: human dignity in technological perspective / Elaine L. Graham -- Dying with dignity? / Gerhard Sauter -- The Multidimensionality of Human Dignity: -- Human dignity, human complexity, and human goods / Don S. Browning -- Theological anthropology versus anthropological reductionism / Michael Welker